MISTERI TULANG EKOR DALAM KAJIAN QSM - Mayla Dianatul Haq; Arini Salma Fuadina; Muna Faoziyatun (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to analyze the concept of 'Ajbu adz-Dzanab (the coccyx) in the traditions of Prophet Muhammad (Hadith), examine the formation and function of the coccyx from the perspective of modern embryology, and explain its relevance to the concept of human resurrection within the framework of the integration of Islam and science. This research employed a qualitative approach using a library research design. Data were collected from the Hadith, Qur'anic verses, classical and contemporary Qur'anic commentaries, textbooks on embryology and anatomy, and scientific journal articles discussing the coccyx from both Islamic and scientific perspectives. Data collection was conducted through documentation techniques, while data were analyzed using content analysis by comparing the Hadith, scholarly interpretations, and contemporary scientific findings. The findings indicate that the Hadith describes the coccyx as a fundamental part of human creation and the basis for the reconstruction of the human body on the Day of Resurrection. Modern embryological studies reveal that human body formation begins with the primitive streak, which subsequently regresses toward the coccygeal region, while anatomical studies confirm that the coccyx performs essential biomechanical functions. The study concludes that there is a conceptual relationship between the Hadith, the Qur'an, and modern scientific findings, although each possesses a different epistemological scope. This integrative approach demonstrates that religion and science can complement one another in understanding the nature of human creation.